Pengalihan Fungsi Pengawasan Lembaga Perbankan Dari Bank Indonesia Ke Otoritas Jasa Keuangan - Zulfi Diane Zaini (Law Faculty of Universitas Bandar Lampung, 2014)
FSA was formed with the aim that the overall activity in the financial services sector can be held on a regular basis, fair, transparent, and accountable financial system which is able to realize sustainable growth and stable, and able to protect the interests of consumers and society. Research issues that will be discussed in this paper is: how Duties and Functions of the Financial Services Authority in Indonesian Banking service activities and how the control mechanisms of the Financial Services Authority carried out activities in the Indonesian banking services. Based on the results of the study discusses the duties and functions of the Financial Services Authority of the activities of banking services in Indonesia, papat views of coordination between the regulation and supervision, banking and monetary authority with fiscal authorities to strengthen early detection of the direction and trends in financial markets has also become very important. Conducted surveillance mechanism against the Financial Services Authority in the Indonesian banking services activities, Conduct banking supervision, the financial system is able to realize sustainable growth and stable and able to protect the interests of consumers and society as referred to in Act Number 20 Year 2011.